P.090 A case of delayed uncal herniation secondary to external hydrocephalus post intraventricular surgery. (5th June 2019) - Ellenbogen, Y; Yang, K; Lu, J; Reddy, K
Abstract : Background: Central neurocytoma's are typically located in the lateral ventricles and are optimally treated with surgical resection. Surgical entry into the ventricles are associated with a number of complications, including subdural hygroma and shunt-dependent hydrocephalus.Methods: We report a patient who developed acute bilateral uncal herniation from progessively enlarging subdural hygromas following intraventricular tumour resection.Results: A 60-year-old female underwent minimally invasive transcortical transventricular resection of an intraventricular CN. The patient's postoperative course was complicated by repeated presentations to the emergency department due to persistent and intractable nausea and headaches, without focal neurological deficits. Imaging demonstrated small bilateral subdural hygromas. The patient eventually presented with acute deterioration in her level of consciousness with clinical and radiologic evidence of bilateral uncal herniation, requiring urgent insertion of a subdural drain to treat elevated intracranial pressure (ICP). After insertion of a ventriculoperitoneal shunt, the patient was discharged in stable condition and is currently followed by the multi-disciplinary neuro-oncology team.Conclusions: Bilateral subdural hygroma could mask underlying external hydrocephalus post transventricular surgeries. Patients who are symptomatic from bilateral subdural hygromas after transventricular resection of tumors should be carefully monitored for radiographic or clinical progression, in order to avoid acute deterioration caused by elevated ICP.